(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2011)
This paper describes the studies performed with the candidate Certified Reference Material (CRM) of captopril, the first CRM of an active pharmaceutical ingredient (API) in Brazil, including determination of impurities (organic, inorganic and volatiles), homogeneity testing, short- and long-term stability studies, calculation of captopril content using the mass balance approach, and estimation of the associated measurement uncertainty.